Self-identified Black Race as a Risk Factor for Intraocular Pressure Elevation and Iritis Following Prophylactic Laser Peripheral Iridotomy. Issue 4 (4th April 2022) - Adetunji, Modupe O.; Meer, Elana; Whitehead, Gideon; Hua, Peiying; Badami, Avni; Addis, Victoria; Gorry, Thomasine; Lehman, Amanda; Sankar, Prithvi S.; Miller-Ellis, Eydie; Ying, Gui-Shuang; Cui, Qi N.
Abstract : Précis: In primary angle closure suspects (PACS), self-identified Black race was a risk factor for intraocular pressure (IOP) elevation and iritis following laser peripheral iridotomy (LPI). Laser type was not associated with either immediate post-LPI IOP elevation or iritis in multivariate analysis. Purpose: The aim was to determine the impact of laser type and patient characteristics on the incidence of IOP elevation and iritis after LPI in PACS. Materials and Methods: The electronic medical records of 1485 PACS (2407 eyes) who underwent either neodymium-doped yttrium-aluminum-garnet or sequential argon and neodymium-doped yttrium-aluminum-garnet LPI at the University of Pennsylvania between 2010 and 2018 were retrospectively reviewed. Average IOP within 30 days before LPI (baseline IOP), post-LPI IOP within 1 hour, laser type, laser energy, and the incidence of new iritis within 30 days following the procedure were collected. Multivariate logistic regression accounting for intereye correlation was used to assess factors associated with incidence of post-LPI IOP elevation and iritis, adjusted by age, sex, surgeon, and histories of autoimmune disease, diabetes, and hypertension. Results: The incidence of post-LPI IOP elevation and iritis were 9.3% (95% confidence interval: 8.1%-10.5%) and 2.6% (95% CI: 1.9%-3.2%), respectively. In multivariate analysis, self-identified Black race was a risk factor for both IOP elevation [odds ratio (OR): 2.08 compared with White; P =0.002] and iritis (OR: 5.07; P <0.001). Higher baseline IOP was associated with increased risk for post-LPI IOP elevation (OR: 1.19; P <0.001). Laser type and energy were not associated with either post-LPI IOP elevation or iritis ( P >0.11 for all). Conclusions: The incidence of immediate IOP elevation and iritis following prophylactic LPI was higher in Black patients independent of laser type and energy. Heightened vigilance and increased medication management before and after the procedure are suggested to help mitigate these risks.